5-HT function in rodent models of anxiety - Wright, Ian Kevin (1991)
This thesis attempts to determine the role of 5-hydroxytryptamine (5-HT) in rodent models of anxiety. Using the elevated X-maze it was possible to detect dose-dependent anxiolytic effects of diazepam and dose-dependent anxiogenic effects of FG 7142 (a β-carboline derivative) and idazoxan. The fear-potentiated acoustic startle paradigm also detected the effects of these compounds but the results were neither dose-dependent nor very reproducible. Using the X-maze the 5-HT1A receptor partial agonist ipsapirone had no effect after either acute or chronic treatment, while both the 5-HT2 receptor antagonist, ritanserin, and the 5-HT3 receptor antagonist, ondansetron, had anxiolytic activity after chronic treatment.